Hypersensitivity in the lungs is responsible for acute respiratory failure in COVID‐19 patients: Case series of patients who received high‐dose/short‐term methylprednisolone. Issue 7 (27th August 2021) - Chen, Meizhu; Tu, Changli; Tan, Cuiyan; Zheng, Xiaobin; Sun, Fengfei; Liang, Yingjian; Shi, Honglei; Wu, Jian; Huang, Yiying; Wang, Zhenguo; Wang, Kongqiu; Lin, Minmin; et al.
Abstract: Background: COVID‐19 is a highly contagious respiratory disease caused by the SARS‐CoV‐2 virus. Patients with severe disease have a high fatality rate and face a huge medical burden due to the need for invasive mechanical ventilation. Hypoxic respiratory failure is the major cause of death in these patients. There are currently no specific anti‐SARS‐CoV‐2 drugs, and the effect of corticosteroids is still controversial. Methods: The clinical data of 102 COVID‐19 patients, including 27 patients with severe disease, were analyzed. The serum levels of total IgE and anti‐SARS‐CoV‐2 specific IgE were compared in healthy controls and COVID‐19 patients, changes in the level of anti‐SARS‐CoV‐2 specific IgE and clinical response to methylprednisolone (MP) treatment were analyzed, and the effect of high‐dose/short‐term MP therapy for patients with critical illness and respiratory failure was determined. Results: COVID‐19 patients had elevated serum levels of anti‐SARS‐CoV‐2 specific IgE, and patients with severe disease, especially critical illness, had even higher levels. Application of short‐term/high‐dose MP significantly reduced the level of these IgE antibodies and also blocked the progression of hypoxic respiratory failure. Hypoxic respiratory failure in patients with COVID‐19 is related to pulmonary hypersensitivity. Conclusions: Hypersensitivity in the lungs is responsible for acute respiratory failure in COVID‐19 patients. Application of high‐dose/short‐term MP appears to be an effective life‐saving method for COVID‐19 patients who have hypoxic respiratory failure.